Balanço de pagamentos e taxa de câmbio no Brasil 1961/1982: uma visão monetária - Silva, José Renato Leite Pereira da (1985)
In this paper, the author tri~s to analyse the pressure put on the Brazilian balance of payments by the external economic bottleneck and to examine the extent to which the government decision to search the external equilibrium through severe measure to control the domestic credit constitued an adequa te alternative.The paper màkes a revision of the historical and institucional aspects of the Brazilian monetary andexchange policy and makes a study of the balance of payments theo r í es v- The analysis is based upon the Girton and Ropper's approach to the monetary model adapted for the Brazilian case in1961-1982. For the tests, it was used the ''EconometricSoftware Package - ESP _li. In the .final explanations. it is assumed that the model met the aim oÍ the paper, thus explaining the facts related to balance of payments, exchange rate.